Seguimiento a profesionales de la carrera de Gestión Administrativa de la Universidad Estatal de Bolívar en los años 2014-2016 con fines de evaluación a la formación profesional - Arévalo Tualombo, Fanny Magdalena (2016)
The research is structured by a few sections starting with the theme "Follow-up of professionals in the career of Administrative Management of the State University of Bolivar in the years 2014-2016 for purposes of evaluation of vocational training." The problem, how does the evaluation of vocational training affect the work performance of the graduates of the administrative management career at Bolivar State University in the years 2014-2016? General Objective.- Conduct a follow-up study of the professionals of the Administrative Management career of the Bolivar State University, in the years 2014-2016, for the purpose of evaluating professional training, to strengthen the work performance of the graduates and Graduates The Hypothesis.- Will the evaluation of the professional training of graduates and graduates of the Administrative Management career at the Bolivar State University in the years 2014-2016 improve the work performance? Consequently, the theoretical framework responds to the two variables of the hypothesis. Evaluation to the professional formation and Work performance: Methodology. - The research designs are: Historical - logical, inductive, deductive and synthetic, by purpose, by level, by place, by origin, by time dimension, by time of occurrence; The Technique and Instrument that was used for the research was the survey and was applied to graduates and graduated professionals in the years 2014 - 2016. The type of research is quanti - qualitative. Developing a process of action-reflection-action, which allowed to overcome the problem posed through the strategies of change, implementing a proposal for intervention.